1971
DOI: 10.1113/jphysiol.1971.sp009507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold, eating, efferent nerve stimulation and angiotensin on heart rate in sheep before and after autonomic blockade

Abstract: SUMMARY1. Effects of the natural stimuli of cold exposure and feeding on heart rate were tested in conscious sheep in which blockade of the cardiac efferent nerves was achieved by administration of propranolol and atropine. Effects of direct nerve stimulation, isoproterenol and angiotensin on heart rate before and after autonomic blockade were studied in acute preparations anaesthetized with pentobarbitone sodium.2. Propranolol reduced the extent of cardioacceleration induced both by exposure to cold and by ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
3
5
0
Order By: Relevance
“…The increase in HR of the cat during eating was reduced by propranolol, which is similar to previous reports on the dog (VATNER et al, 1970a;HAYS and WEBSTER, 1971). The effect of propranolol on the HR response to eating suggested that the acceleration of HR may be evoked at least partially by an increase in sympathetic nerve activity.…”
Section: Discussionsupporting
confidence: 90%
“…The increase in HR of the cat during eating was reduced by propranolol, which is similar to previous reports on the dog (VATNER et al, 1970a;HAYS and WEBSTER, 1971). The effect of propranolol on the HR response to eating suggested that the acceleration of HR may be evoked at least partially by an increase in sympathetic nerve activity.…”
Section: Discussionsupporting
confidence: 90%
“…The present experiments show that this is the case and thus provide further support for the hypothesis of Hays & Webster (1971) that angiotensin is directly responsible for some of the changes in cardiac function observed during eating in the sheep.…”
Section: Discussionsupporting
confidence: 74%
“…Hays & Webster (1971) suggested that the tachycardia accompanying eating in sheep might be due to a direct cardioaccelerator action of angiotensin, since plasma angiotensin levels are elevated during eating (BlairWest & Brook, 1969) and angiotensin was shown to have a cardioaccelerator effect after surgical and pharmacological inhibition of autonomic influences on the heart of anaesthetized sheep (Hays & Webster, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that vagal withdrawal is likely to induce only a modest rise in heart rate in sheep. Previous studies both from our laboratory (unpublished data) and from the literature (Hays & Webster 1971, Lumbers & Yu 1999 show that i.v. atropine or vagal section increases heart rate in sheep by w20-30 bpm with the maximum heart rates observed following withdrawal of vagal tone being 110-120 bpm.…”
Section: Discussionmentioning
confidence: 95%